SPATIAL PATTERN OF SULFUR DIOXIDE DISPERSION AND AFFECTED SETTLEMENT AREAS IN SERANG REGENCY BANTEN PROVINCE - Putra, Ahmad Pratama (Jurnal Sains dan Teknologi Mitigasi Bencana, 2020)
In Serang Regency, pollutants and air emissions are produced by industrial activities, including Sulfur Dioxide (SO2) gas. SO2-polluted air causes problems to the human respiratory system. This study examine the spatial pattern of SO2 gas dispersion and its impact on settlements in Serang Regency using geostatistic and Inverse Distance Weighting (IDW) method in Arc GIS. Based on the results of ambient air quality measurements in Serang Regency, which have been measured by the Serang Regency Environmental Agency from 2015 - 2019 for the SO2 parameter, it can be seen that none of them exceed the standard of the PP No. 411999 concerning Air Pollution Control. The results of spatial analysis of gas dispersion show tendencies of high gas concentration in industrial zones, which indicate the contribution of gases from industrial business activities in several monsoons. The most extensive settlement affected by SO2 gas with the highest value of 40-50 µg / Nm3 is on Cikande District covering an area of 3.173,77 Ha which occurs during the west monsoon from December to February.